VALUE OF THERAPEUTIC EQUIVALENCE IN SUBSTITUTION OF ORIGINAL DRUG WITH GENERIC BY EXAMPLE OF FOSINIPRIL - N. P. Kutishenko; S. Yu. Martsevich; Zh. D. Kobalava; E. K. Shavarova (Столичная издательская компания, 2016)
Aim. To study the therapeutic equivalence of original and generic fosinopril in patients with arterial hypertension (HT) of 1-2 degrees, and to evaluate the cost effectiveness of original drug substitution with generic. Material and methods. Patients (n=36) with HT of 1-2 degree aged 41-82 years and disease duration up 3 to 22 years included in an open, crossover , randomized trial. All patients had two courses of treatment: with generic (Fosicard) and the original drug (Monopril); sequence of courses was determined by randomization. Wash-out period (10-14 days) preceded each course. Treatment duration was 6 weeks; drugs were administered QD; initial dose - 10 mg/day. Blood pressure (BP) and heart rate (HR) were evaluated at the end of the wash-out period, and in 2, 4 and 6 weeks of therapy. In case of ineffective BP control (>140/90 mm Hg) hydrochlorothiazide 12.5 mg was added initially and dose fosinopril was increased up to 20 mg/day next. Results. Patients in groups were comparable by basic clinical parameters. Both fosinopril based drugs have comparable antihypertensive effect. Differences between their effect on systolic and diastolic BP as well as HR at all steps of treatment were not significant. The individual analysis revealed a tendency to more pronounced Monopril antihypertensive effect compared with Fosicard, but the differences were not significant. An average dose of Monopril was 11.8±3.9 mg/day , and Fosicard - 13.2±4.7 mg/day (p=0.13); the rate of monotherapy with both drugs of fosinopril at dose of 10 mg/day was similar (in 41% and 44% of patients, respectively); the rate of combined therapies with various composition differed insignificantly. Reduction in BP <140/90 mmHg was recorded at the end of the study in 29 (85.3%) patients treated with Monorpil and in 27 (79.4%) - Fosicard (p=0.52). Both drugs showed a good safety profile. Conclusion. Fosicard or its combination with hydrochlorothiazide is therapeutically equivalent to original drug (Monopril) or its combination with hydrochlorothiazide.